Electrochemical detection of cystatin C by oriented antibody immobilization on streptococcal protein G–modified ZIF-8-Cu1−xNix(OH)2@Cu core-shell nanostructured electrode. (January 2023) - Chakraborty, T.; Das, M.; Lin, C.Y.; Kao, C.H.
Abstract: Herein, we prepared a novel nanostructure involving Cu shell on Zeolitic imidazolate frameworks (ZIF-8) and Cu1−x Nix (OH)2 composite (ZIF-8-Cu1−x Nix (OH)2 @Cu) combining sol-gel and co-precipitation method. The morphology, stoichiometry, and structure of the nanocomposite were elucidated by various physicochemical analyses. A poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) coated indium tin oxide (ITO) was modified with the synthesized ZIF-8-Cu1−x Nix (OH)2 @Cu nanoparticles (NPs) to obtain an efficient electrode for further antibody immobilization. The ZIF-8-Cu1−x Nix (OH)2 @Cu/PEDOT:PSS/ITO was applied for the detection of cystatin C, a promising biomarker of chronic kidney disease (CKD). The electrode was functionalized by streptococcal protein G (SPG) to bind the Fc region of anti-cystatin C in an oriented manner. The synergistic catalytic activities, high surface coverage, enhanced electroactive sites, and excellent redox properties of the proposed electrode lead to excellent electrochemical sensing. The proposed sensor obtained a much lower detection limit (33 pg/mL) for a linear range of 0.1 ng/mL to 1, 000 ng/mL with high selectivity, stability, and reproducibility compared with bare ZIF-8/PEDOT:PSS/ITO-based immunosensor. The clinical feasibility of the sensor was confirmed by measuring the human serum in the presence of different concentrations of cystatin C. This work demonstrates a new and facile approach to fabricating a metal-organic framework (MOF) –based nanoimmunosensor for cystatin C, which has significant importance in diagnosing the renal failure. Graphical abstract: Image 1 Highlights: ZIF-8-Cu1−x Nix (OH)2 -based biosensor was developed to detect cystatin C. The detection limit of the sensor was 33 pg/mL for a wide linear range. The senor showed high anti-interference to other biomolecules. The immunosensor achieved excellent recovery rates in human serum with cystatin C.